2013
DOI: 10.1016/j.ridd.2013.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Fine and gross motor skills differ between healthy-weight and obese children

Abstract: Within the obesity literature, focus is put on the link between weight status and gross motor skills. However, research on fine motor skills in the obese (OB) childhood population is limited. Therefore, the present study focused on possible weight related differences in gross as well as fine motor skill tasks. Thirty-four OB children (12 ♀ and 22 ♂, aged 7-13 years) were recruited prior to participating in a multidisciplinary treatment program at the Zeepreventorium (De Haan, Belgium). Additionally, a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
4
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 34 publications
9
107
4
12
Order By: Relevance
“…Evidence from several cross-sectional studies with large samples of children, adolescents, and young adults clearly demonstrates an inverse association (r = -0.20 to r = -0.62) between both factors using various MC and weight status measures [7,42,[73][74][75][76]. In addition, differences in MC levels of overweight/obese children as compared with healthy weight peers are more evident in tasks requiring manipulation of total body mass [74,77,78]. Inverse associations between MC and weight status emerge at pre-school age [76,79,80] and become stronger during elementary school years [42,75].…”
Section: Motor Competence and Weight Statusmentioning
confidence: 99%
“…Evidence from several cross-sectional studies with large samples of children, adolescents, and young adults clearly demonstrates an inverse association (r = -0.20 to r = -0.62) between both factors using various MC and weight status measures [7,42,[73][74][75][76]. In addition, differences in MC levels of overweight/obese children as compared with healthy weight peers are more evident in tasks requiring manipulation of total body mass [74,77,78]. Inverse associations between MC and weight status emerge at pre-school age [76,79,80] and become stronger during elementary school years [42,75].…”
Section: Motor Competence and Weight Statusmentioning
confidence: 99%
“…For instance, reduced postural stability while standing leads to longer movement time and deceleration phase during a goal-directed movement in obese [2]. Furthermore, the impact of body weight on the execution of functional motor tasks relative to postural control among children have been well documented, particularly for the 6-7 year old age group, where motor development first reaches maturity [5][6][7][8][9][10][11]. Many of these studies investigated the effect of obesity on gross motor skills such as walking backwards along balance beams of decreasing width, moving sideways on wooden boards, one-legged hopping over a foam obstacle, and two-legged jumping from side to side [12,13], or on fine motor skills such as a peg placing task [6].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy adults, stress has shown to impair motor function, [16][17][18] increase muscle fatigability 19,20 and hinder muscular and cardiovascular recovery, 21 which can ultimately put stressed workers at greater risks of developing musculoskeletal disorders and cardiovascular diseases. 22,23 Recent investigations have suggested that obesitylinked structural changes in the brain 24 can result in slower information processing speed and reduce efficiency of sensory integration 25 that has shown to impair both cognitive 26 and motor functions. 11 Because obese adults perceive higher stress levels at work compared with their normal-weight colleagues, 13,27,28 it is likely that stress, due to intense workload, may contribute to greater muscle fatigability in this population, though this has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%